A blended community of inquiry approach: the usage of social network as a support for Course Management System - Lahad, N.A. (2012)
This research offers an opportunity to investigate the usage of Social Network Site (SNS) as a support for Course Management Systems (CMS) in Community of Inquiry (Col) model in a blended learning. In order to investigate the largely unexplored benefits of educational SNSs, the researchers used SNS to support CMS for students to evaluate the influence of using non-commercial social network upon the perception of students learning experience in blended learning. Although SNSs provide great Web 2.0 learning applications that can support teaching and learning, the advantages of these websites are oftentimes ignored. There are currently few researches regarding the educational benefits of SNSs in teaching and learning. The researchers used pre-questionnaire and post-questionnaire for assessing the level of students' learning experience before and after using SNS based on the Col model. Through statistical analysis by using t-test analysis, the usage of social network is proven to enhance students' learning experience. And lastly, the guidelines of this research study can help lecturers make a decision to use SNS as a support of CMS for teaching and learning.